LABORATORY EXAMS IN PREGNANT WOMEN: IMPORTANCE OF CARE - Roque Garcia, Fernanda; Evelly da Silva Olanda, Débora; Fernandes Filgueiras, Mateus; de Oliveira Souza, Eclésia; Thallyta Alexandre de Pontes, Arunna; Carolina Salustino dos Santos, Maria; Claudino do Nascimento, Nathalia; Allyson Gomes Ferreira, Jefferson; Costa Soares Silva, Talita; Casado de Freitas Silva, Rosany; da Silva Caldas, Walissioneide (Health and Society, 2022)
During prenatal care, professionals should request laboratory tests immediately, seeking to identify cases of viral and/or bacterial infections that bring future complications or are transmitted vertically to the fetus. Reflection study, built in 2022, from reading articles, abstracts and books. It was noticed that routine laboratory tests in prenatal care are of paramount importance and must be requested according to the guidelines protocol in the first consultation.